1996
DOI: 10.1097/00006216-199602030-00007
|View full text |Cite
|
Sign up to set email alerts
|

Power in Practice: A Study of Nursing Authority and Autonomy

Abstract: Power and politics need to be translated into practice through development of authority and autonomy within the staff nurse role. The purpose of the research described was to identify and compare aspects of agreement or disagreement between nurse leaders and staff about staff nurses' authority and autonomy to deliver patient care. Findings indicated that significant differences exist between staff nurses' and nurse leaders' sense of staff nurse autonomy, and importance of authority and autonomy, differences th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
2
1

Year Published

1997
1997
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 0 publications
3
35
2
1
Order By: Relevance
“…For instance, ICU patients require high-level technical devices such as ventilators for treatment. This increases complexity of care and necessitates increased nurse autonomy and PDM (Blanchfield & Biordi, 1996;Morrison, Beckmann, Durie, Carless, & Gillies, 2001). Relationships between type of unit and both medication errors and patient falls are also apparent.…”
Section: Nursing Unit Characteristicsmentioning
confidence: 99%
“…For instance, ICU patients require high-level technical devices such as ventilators for treatment. This increases complexity of care and necessitates increased nurse autonomy and PDM (Blanchfield & Biordi, 1996;Morrison, Beckmann, Durie, Carless, & Gillies, 2001). Relationships between type of unit and both medication errors and patient falls are also apparent.…”
Section: Nursing Unit Characteristicsmentioning
confidence: 99%
“…While the literature indicates that autonomy is a highly desirable nursing role attribute, 7,9,21,38 the findings of this study suggest that contextual and social forces act as enablers or barriers to nurses demonstrating autonomous behavior. Oncology primary nurses gauged their level of autonomy by their familiarity with the physician and the specific patient population.…”
Section: Nurse Autonomy In Cancer Carementioning
confidence: 54%
“…10,24Y26,28 Professional nurse autonomy has been identified as a key indicator of quality healthcare environments. 12,22 Studies have shown that perceived autonomy is a strong predictor of nurse job satisfaction 7,10,22,34,39,41 and that autonomy and job satisfaction are linked to job retention. 39,40,43 In the present study, oncology primary nurses shared how they would be less likely to stay on the job if they did not have job satisfaction.…”
Section: Nurse Autonomy In Cancer Carementioning
confidence: 99%
See 1 more Smart Citation
“…An increase in formal and informal power would lead to an increase in nurses' access to empowerment structures, including information, support and resources. Blanchfield and Biordi (1996) found that the type of organization in which nurses were employed influenced their experiences of authority and autonomy. 'It is possible that organizational variables such as size, governance, management style, organizational culture, policies, and professional collaboration might be predictors of authority and autonomy, rather than demographic variables'.…”
Section: Concepts Of Power From the Health Literaturementioning
confidence: 99%